Alcohol Use Disorder and Heavy Episodic Drinking in Rural Communities in Cambodia: Risk Factors and Community-Perceived Strategies. (November 2015) - Yeung, Wesley; Leong, Wei-Yee; Khoun, Kimsong; Ong, Warren; Sambi, Sundesh; Lim, Su-Min; Bieber, Bill; Wilder-Smith, Annelies
Alcohol misuse is increasing in Southeast Asia. We investigated the extent of and risk factors for alcohol use disorder (AUD) and heavy episodic drinking (HED) in a rural community in Cambodia. We also attempted to explore the communities' perception of alcohol misuse and elicited potential community-based strategies to address the alcohol problem. A mixed-methods study design was used, combining a cross-sectional questionnaire survey with qualitative interviews (focus group discussions and key informant interviews). AUD and HED were measured using the AUDs Identification Test Alcohol Consumption questionnaire. The prevalence of AUD and HED was high: 25% and 31%, respectively. Male sex, younger age, and increasing income were significant risk factors. The communities were well aware of the harmful effects of alcohol, expressed the importance of implementing community-based measures, and proposed various community-led solutions. Evidence-based strategies that are culturally appropriate, accepted, and driven by communities are urgently needed.